Impact of antimicrobial stewardship fee on prescribing for Japanese pediatric patients with upper respiratory infections - Yuichi Muraki; Yoshiki Kusama; Masaki Tanabe; Kayoko Hayakawa; Yoshiaki Gu; Masahiro Ishikane; Daisuke Yamasaki; Tetsuya Yagi; Norio Ohmagari (BMC, 2020)
Abstract Background In 2018, the Japanese medical reimbursement system was revised to introduce a fee for the implementation of an antimicrobial stewardship (AS) fee for pediatric patients. The purpose of this study was to evaluate physicians' prescription behavior following this revision. Methods We conducted a retrospective observational study from January 1, 2017 to September 30, 2018 of pediatric (< 15 years) outpatients with upper respiratory tract infections (URIs). To assess the pattern of antibiotic prescription for the treatment of pediatric URIs before and after the introduction of the AS fee, we extracted data on pediatric URIs, diagnosed during the study period. Patients were divided based on whether medical facilities claimed AS fees. We defined antibiotic use as the number of antibiotics prescribed, and evaluated the proportion of each class to the total number of antibiotics prescribed. We also recorded the number of medical facilities that each patient visited during the study period. Results The frequency of antibiotic prescription decreased after AS fee implementation, regardless of whether the facility claimed the AS fee, but tended to be lower in facilities that claimed the fee. Additionally, the frequency of antibiotic prescription decreased in all age groups. Despite the reduced frequency of antibiotic prescription, consultation behavior did not change. Conclusions The AS fee system, which compensates physicians for limiting antibiotic prescriptions, helped to reduce unnecessary antibiotic prescription and is thus a potentially effective measure against antimicrobial resistance.